2021
DOI: 10.1111/ctr.14277
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive diagnostic imaging tests largely underdiagnose cardiac cirrhosis in patients undergoing advanced therapy evaluation: How can we identify the high‐risk patient?

Abstract: Background Patients with liver cirrhosis are generally considered ineligible for isolated cardiac transplantation or left ventricular assist device (LVAD) implantation. The aim of this retrospective study is to explore the diagnostic value of abdominal ultrasound, computed tomography scan (CT scan) and liver‐spleen scintigraphy to detect the presence of cirrhosis in patients with advanced heart failure. Methods Among 567 consecutive patients who underwent pre‐transplantation or LVAD evaluation, 54 had a liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In our case, a liver biopsy was required to rule out liver cirrhosis. A previous study demonstrated that imaging alone had limited sensitivity for liver cirrhosis in pretransplant assessment [13].…”
Section: Discussionmentioning
confidence: 99%
“…In our case, a liver biopsy was required to rule out liver cirrhosis. A previous study demonstrated that imaging alone had limited sensitivity for liver cirrhosis in pretransplant assessment [13].…”
Section: Discussionmentioning
confidence: 99%
“… Liver imaging : In patients whose clinical history and/or laboratory investigations suggest hepatic dysfunction, screening for fibrosis or cirrhosis via ultrasonography or CT scan (COR I, LOE C) is necessary. Since fibrosis in the absence of significant portal hypertension may not be a contraindication to LVAD implantation [ 59 ], especially in the case of a normal hepatic synthetic capacity, a consultation with a hepatologist is indicated in such patients (COR I, LOE C). Conversely, cirrhosis or advanced hepatic dysfunction represents a contraindication to LVADs.…”
Section: Assessment Of Patientsmentioning
confidence: 99%